2007
DOI: 10.1063/1.2794711
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and magnetoelastic properties of Cr-substituted cobalt ferrite

Abstract: We have investigated the magnetic and magnetoelasticproperties of a series of Cr-substituted cobaltferriteCoCrxFe2−xO4 (x=0.0-0.79) samples. Substitution of Cr for some of the Fe in cobaltferrite reduced the Curie temperature, and the effect is more pronounced than that observed in Mn-substituted cobaltferrite samples. Cr substitution also caused the maximum magnetostriction to decrease at a greater rate than substitution of the same amount of Mn. The maximum of the strain derivative, dλ/dH, was reached for x=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…However, the highest maximum strain obtained for the sample is very low as 150 ppm. Enhancement in the strain sensitivity is reported after substitution of metal ions in the cobalt ferrite lattice, but at the cost of the magnetostriction strain [13][14][15][16][17]. It has been shown that the strain sensitivity can be enhanced, without affecting the magnetostriction coefficient, for sintered Mn-substituted cobalt ferrite made from nanosized powders [18].…”
Section: Introductionmentioning
confidence: 94%
“…However, the highest maximum strain obtained for the sample is very low as 150 ppm. Enhancement in the strain sensitivity is reported after substitution of metal ions in the cobalt ferrite lattice, but at the cost of the magnetostriction strain [13][14][15][16][17]. It has been shown that the strain sensitivity can be enhanced, without affecting the magnetostriction coefficient, for sintered Mn-substituted cobalt ferrite made from nanosized powders [18].…”
Section: Introductionmentioning
confidence: 94%
“…Rare-earth ions substitution into Fe 3+ -site in AB 2 O 4 type spinel ferrites has been reported to induce structural distortion and strain and thus significantly modifies the electrical and magnetic properties [16][17][18][19][20][21]. Rare-earth (Ho, Er, Tm, Yb, Lu) ion doping/substitution into cobalt ferrite tend to decrease the room-temperature magnetization as well as the Curie point [22].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies on CoFe 2 O 4 have been carried out by various research groups [14][15][16][17][18][19][20][21][22], but systematic studies on the electrical, magnetic, and thermal studies of nanosized CoFe 2 O 4 are limited. The substitution of other metals in cobalt ferrite has been proposed inorder to tailor the magnetic, electrical, and magnetomechanical properties [15,16]. To the best of our knowledge, limited research groups have been reported on Cd CoFe 2 O 4 system.…”
Section: Introductionmentioning
confidence: 99%